Developmental transitions in body color in chacma baboon infants: Implications to estimate age and developmental pace. Issue 1 (26th August 2020) - Dezeure, Jules; Dagorrette, Julie; Baniel, Alice; Carter, Alecia J.; Cowlishaw, Guy; Marshall, Harry H.; Martina, Claudia; Raby, Cassandra L.; Huchard, Elise
Abstract: Objectives: In many primates, one of the most noticeable morphological developmental traits is the transition from natal fur and skin color to adult coloration. Studying the chronology and average age at such color transitions can be an easy and noninvasive method to (a) estimate the age of infants whose dates of birth were not observed, and (b) detect interindividual differences in the pace of development for infants with known birth dates. Materials and Methods: Using a combination of photographs and field observations from 73 infant chacma baboons ( Papio ursinus ) of known ages, we (a) scored the skin color of six different body parts from pink to gray, as well as the color of the fur from black to gray; (b) validated our method of age estimation using photographic and field observations on an independent subset of 22 infants with known date of birth; and (c) investigated ecological, social, and individual determinants of age‐related variation in skin and fur color. Results: Our results show that transitions in skin color can be used to age infant chacma baboons less than 7 months old with accuracy (median number of days between actual and estimated age = 10, range = 0–86). We also reveal that food availability during the mother's pregnancy, but not during lactation, affects infant color‐for‐age and therefore acts as a predictor of developmental pace. Discussion: This study highlights the potential of monitoring within‐ and between‐infant variation in color to estimate age when age is unknown, and developmental pace when age is known.